System of and Solution for Pay-As-You-Use (PAYU) and Automation of LPG Cylinder Supply Chain through Internet of Things Based Real Time Uses and Inventory Data Analysis - Khan, Vishal C; Nitheesh Kumar, P; Chatterjee, Mohinish; Kumar, Abhishek; Singh, SK (International Journal of Computer Sciences and Engineering, 2025)
Considering the economics of cooking fuel used by Below Poverty Household in India, the biggest challenge in transition of such household from conventional cooking fuel to clean and modern cooking fuel like LPG is unavailability of price fragmentation and Pay-As-Use features while purchasing LPG. Recent development in the field of Internet of Things has proven stories where assets can be tracked, monitored and controlled remotely. There is huge scope as well as requirement for innovative idea that can bring the principle of mechanical engineering, electrical engineering and data analytics together to achieve the feature of price fragmentation for LPG uses. This paper presents system and solution for tracking real time LPG consumption and inventory data by using Internet of Things (IoT), connecting the different stakeholder of LPG supply chain, analysis and computation of data to automate LPG cylinder booking and delivery practice, make the LPG supply chain transparent at each level and use the data tracking and analysis system to provide “Pay-As-You-Use (PAYU) apparatus to the LPG consumer in general and financially marginal consumers in particular.